Impact of e-leadership on organizational innovation performance: Role of employee followership - Zhong, Lin; Sukpasjaroen, Khunanan; Pu, Ruihui (Decision Making: Applications in Management and Engineering, 2023)
To investigate the influence of E-Leadership on organizational innovation performance (OIP), data from previous studies were analyzed, and a theoretical model containing E-Leadership, employee innovation behavior (EIB), followership, and OIP was constructed using the theoretical frameworks of the Supervisor’s Organizational Embodiment (SOE) theory, social learning theory, and "social man" hypothesis. Subsequently, to investigate the interrelationships of E-Leadership, followership, and OIP, 372 questionnaire responses were collected from workers at representative Chinese foreign export enterprises, and data were analyzed using a manager–employee-matched design. Data analysis showed that: (1) The six dimensions of E-Leadership have a positive impact on OIP, (2) EIB mediates the effect of the six E-Leadership dimensions on OIP, and (3) The effects of E-Communication, E-Change, and E-Tech on EIB are negatively moderated by followership. Therefore, the findings suggest that organizations can improve innovation performance by improving managers’ E-Leadership. At the same time, they should effectively influence employees’ followership to prevent reductions in innovation behavior due to over-compliance with managers. This study not only provides a reference for enterprises to improve their OIP but also promotes theoretical research on E-Leadership.